Synthesis of a novel stabilized basic ionic liquid through immobilization on boehmite nanoparticles: A robust nanocatalyst for biodiesel production from soybean oil. (August 2019) - Hosseini, Shokoufe; Moradi, G.R.; Bahrami, Kiumars
Abstract: A novel ionic liquid, chlorocholine hydroxide (CCH), was first synthesized and then stabilized on boehmite nanoparticles (BNPs-CCH). Variables such as weight percentage of catalyst, methanol to oil molar ratio and reaction time were evaluated to study the catalyst efficiency in the production of biodiesel from soybean oil and methanol. Results showed that the biodiesel yield maximum was obtained in 95.2% for optimal conditions of 11:1, 4.13 wt, 60 °C and 4.4 h for the molar ratio of methanol to oil, weight percentage of catalyst, temperature and reaction time, respectively. In addition, the prepared nanocatalyst was applied 5 times under optimal conditions in order to evaluate the catalyst efficiency. According to the results it still indicated as high efficiency as in the production of biodiesel. Therefore, the strength and durability of the resultant nanocatalyst were confirmed in this research. Highlights: A novel ionic liquid, chlorocholine hydroxide synthesized and stabilized on boehmite. It was used in the production of biodiesel from soybean oil and methanol. Yield was 95.2% for optimal conditions of 11:1 Me/Oil, 4.13 wt%Cat, 60 °C, 4.4 h. Catalyst applied 5 times under optimal conditions and indicated high efficiency. Strength and durability of the resultant nanocatalyst were confirmed.